The Surveillance Database Development of Risk Factor for Dengue Fever in Mataram District Health Office - Sinawan Sinawan; Santi Martini; Windhu Purnomo (Jurnal Berkala Epidemiologi, 2015)
The epidemiological surveillance system of Dengue Hemorrhagic Fever (DHF) currently underway at the Mataram City Health Office has not been able to provide information on the incidence of DHF based on risk factors. Data processing and analysis are also still done manually. The purpose of this study is to develop a database of risk factors for DHF events. This research is action research. This research was conducted at the Mataram City Health Office in West Nusa Tenggara (NTB) province from April 2014 to August 2014. The informants in this study consisted of 3 people, which are the Head of The Disease Prevention and Control Program (P2P), DHF Prevention and Control Program (P2DHF) officers, and Disease Surveillance Officer. The type of data used is primary and secondary data. The database design includes logical and physical design. In the logical design, data normalization, making relationships between data, describing Entity Relationship Diagrams (ERD), and proceed to a physical design by making a database prototype using Epi Info software application. The trial was conducted involving 2 (two) informants. Evaluation of the trial of the surveillance database for risk factors for dengue events, namely by assessing the level of ease, speed, accuracy, and completeness of the resulting data. The results of this study are the existence of a new DHF risk factor surveillance database that can be used easily, quickly, and can produce more accurate information.